Dampak Judi Online terhadap Keharmonisan Rumah Tangga Perspektif Hukum Keluarga di Kota Tual - Aisa Renhoat; Abubakar Kabakoran; Eka Dahlan Uar (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This research, entitled The Impact of Online Gambling on Household Harmony from the Perspective of Family Law in Tual City, aims to: 1) Identify and analyze the economic impact of online gambling on households in Tual City; 2) Examine the socio-cultural factors associated with online gambling practices; and 3) Investigate how these factors affect household harmony. The research method employs a qualitative descriptive approach, with data collection techniques including: 1) Structured/in-depth interviews; 2) Documentation; and 3) Digital media, with a sample of 12 primary respondents. This research uses descriptive analysis techniques that systematically explain the research to provide a comprehensive understanding of the impact of online gambling on household harmony. Many respondents expressed complaints regarding the decline in family income, the occurrence of household conflicts (60%) leading to divorce (30%), debt accumulation, the loss of spousal rights and obligations, poor family economic conditions, and marital status that ultimately remains uncertain and results in disharmonious households. Overall, the research findings confirm the hypothesis that online gambling has a significant negative impact on household harmony in Tual City through mechanisms of economic weakness within families, communication disruption, psychological stress, and the erosion of custom-religion-based social values.